2005
DOI: 10.1128/iai.73.2.1171-1179.2005
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum Increases Collagenase 3 Production and Migration of Epithelial Cells

Abstract: Fusobacterium nucleatum is closely associated with human periodontal diseases and may also be a causative agent in other infections, such as pericarditis, septic arthritis, and abscesses of tonsils and liver. Initiation and outcome of infective diseases depend critically on the host cell signaling system altered by the microbe. Production of proteinases by infected cells is an important factor in pericellular tissue destruction and cell migration. We studied binding of F. nucleatum to human epithelial cells (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 74 publications
3
98
0
Order By: Relevance
“…nucleatum and other Fusobacterium species can elicit host proinflammatory response and possess virulence characteristics that promote their adhesiveness to host epithelial cells (Bachrach et al 2005;Uitto et al 2005) and their ability to invade into epithelial cells (Han et al 2000;Strauss et al 2011). Therefore, our findings of a tumoral enrichment of Fusobacterium spp.…”
Section: Discussionmentioning
confidence: 68%
“…nucleatum and other Fusobacterium species can elicit host proinflammatory response and possess virulence characteristics that promote their adhesiveness to host epithelial cells (Bachrach et al 2005;Uitto et al 2005) and their ability to invade into epithelial cells (Han et al 2000;Strauss et al 2011). Therefore, our findings of a tumoral enrichment of Fusobacterium spp.…”
Section: Discussionmentioning
confidence: 68%
“…Ghosh et al showed that all MAPK (p38, ERK, and JNK) inhibitors showed little or no effect on F. nucleatum cell wall-induced CCL20 secretion in human oral epithelial cells (26). F. nucleatum induces collagenase 3 gene expression in human keratinocytes (HaCaT cells) via a p38-but not ERK-dependent pathway (27). In addition, p38 and JNK, but not NF-B, mediate the induction of human ␤-defensin 2 (hBD-2) production in response to F. nucleatum in gingival epithelial cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 13 anaerobic oral bacterial species, F. nucleatum and necrophorum were among the best inducers of collagenase 3 mRNA levels, a powerful matrix metalloproteinase. This suggests that F. nucleatum may be involved in the pathogenesis of periodontal diseases by activating multiple cell signaling systems that lead to stimulation of collagenase 3 expression and increased migration and survival of the infected epithelial cells (Uitto et al, 2005). A crucial part of the epithelial defense system is the efficient recruitment of professional defense cells, especially of neutrophils, to the infection site.…”
Section: Fusobacterium Nucleatum: a Protective Or An Aggressive Bactementioning
confidence: 99%